Unconventional Branding Strategy: An Analysis Of Aerostreet’s Unique Collaborations From A Creative Marketing Perspective - Rusdianto, Ujang; Saputro, Eko Hadi (Jurnal ISIP: Jurnal Ilmu Sosial dan Ilmu Politik, 2025)
This study explores Aerostreet’s creative co-branding strategy through cross-industry collaborations, particularly with food and beverage brands, to strengthen brand identity and enhance consumer engagement. Guided by Keller’s (2008) Co-Branding Strategy theory, the research examines brand fit, collaboration appeal, and digital communication strategies. Using a qualitative literature review method, this study synthesizes academic works and credible sources to understand the success factors and challenges of Aerostreet. Key findings highlight Aerostreet’s strategic partner selection based on emotional resonance, the use of exclusivity through limited releases, and strong community-based digital engagement. Nevertheless, challenges such as potential brand identity mismatch and speculative pricing were also observed. The study concludes that co-branding if aligned with brand values and communicated effectively, is a powerful tool for local brand development.